IMPLEMENTASI PERDA NOMOR 13 TAHUN 2010 TENTANG KERJASAMA DAERAH KABUPATEN SEMARANG (Studi kasus: Kerjasama dalam Pengelolaan Air Bersih antara PDAM Kabupaten Semarang dengan PT Sarana Tirta Ungaran) - Budiastiwi, Villia Ayu; Hidayat, Zainal; Rengga, Aloysius (Journal of Public Policy and Management Review, 2015)
ABSTRACT The geographic condition in every regional development regions in indonesia causes is not homogeneous on regional development. Therefore, implemented a decentralization that regional local understanding of the conditions and each for its potential can be used. Development in the infrastructure sector one of which became an integral part of national development because infrastructure of the cogs of economic growth. Infrastructure development requires huge cost. So the government has not been able to pay for it own .One of the alternative solution to solve the problems is in cooperation with investors from private sector by working together. One of cooperation with third parties (private) conducted by the district government Semarang is development and management of clean water between PDAM District Semarang with PT Sarana Tirta Ungaran. This partnership model is a Build Operate and Transfer (BOT), concession period of 27 years and as a source of raw water is Tuntang River. The legal framework underlying the implementation of the cooperation policy is Semarang District Regulation No. 13 Year 2010 on Regional Cooperation. This study aims to analyze how the implementation of regional cooperation between PDAM Semarang with PT STU, as well as some of the supporting factors and obstacles in this cooperation. The results of research on the implementation of this cooperation shows two core problems, there are many industries that use underground water for their production needs and condition of the water distribution pipes that are prone to leak. Researchers recommended governmental interference on this problem , for example making a rules of prohibition the uptake of water underground in big amount and in conformance to selling water tariff , in order to be sustainable cooperation and mutual benefit .